1996
DOI: 10.1007/bf02347630
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoaneurysm of the cystic artery associated with upper gastrointestinal bleeding

Abstract: Pseudoaneurysm of the cystic artery is a cause of hemobilia, and is extremely rare, with only eight cases having been reported in the world literature. We report a case of pseudoaneurysm of the cystic artery in a 72-year-old Japanese man. The patient experienced epigastric pain and melena, and was found to have jaundice and liver dysfunction. Repeated gastroendoscopy did not reveal the cause of the alimentary tract bleeding; however, color-Doppler ultrasonography detected an aneurysm of the cystic artery in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 5 publications
0
33
0
1
Order By: Relevance
“…1,2 In the present patient, US showed echogenic material within the gallbladder, and color-Doppler imaging demonstrated a persistent pulsatile flow within the echogenic lesion. These findings strongly suggested that the echogenic material could be a pseudoaneurysm in the gallbladder.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…1,2 In the present patient, US showed echogenic material within the gallbladder, and color-Doppler imaging demonstrated a persistent pulsatile flow within the echogenic lesion. These findings strongly suggested that the echogenic material could be a pseudoaneurysm in the gallbladder.…”
Section: Discussionmentioning
confidence: 90%
“…[1][2][3][4][5][6][7][8][9] However, pseudoaneurysm of the hepatic artery that ruptured into the gallbladder may be very rare, and in our survey of the literature, the present case report is the first case. The detailed mechanism of the pseudoaneurysm remains speculative.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Pseudoaneurysms of the cystic artery are rare possibly because early thrombosis of the cystic artery is considered to be a reaction of the inflammatory process [8]. However, the pseduoaneursym may have formed in our patient due to his over-anticoagulated state.…”
Section: Discussionmentioning
confidence: 71%
“…If endoscopy reveals bleeding through the papilla of Vater, haemobilia could be more readily diagnosed [8]. It is possible to miss bleeding from the papilla in patients with haemobilia as it may be intermittent in nature or simultaneous rupture into the duodenum may provide an alternative route for the blood to come out [7].…”
Section: Discussionmentioning
confidence: 99%